Direct electron detection for TEM with column parallel CCD - Moldovan, G; Jeffery, B; Nomerotski, A; Kirkland, A (2009)
Step improvements in electron detectors are needed for transmission electron microscopes (TEM) to take full advantage of latest developments in electron optics and electron sources. This work presents beam tests performed with column parallel charge-coupled devices (CPCCD) and discusses measured cluster properties. Excellent signal-to-noise ratio is found, demonstrating that CPCCD are well suited for TEM. Large variations in cluster-integrated intensity and size are observed, attributed to the strong scattering of 120-200 keV electrons in silicon. Spatial momentum analysis of clusters reveals strong asymmetry indicating that position resolution could be limited for certain cluster shapes. © 2009 Elsevier B.V. All rights reserved.